Design And Development Of A Fixed-Wing Vertical Take-Off And Landing Unmanned Aerial Vehicle - Wong, Seng Man (Universiti Sains Malaysia, 2018)
The interest in building hybrid Unmanned Aerial Vehicles (UAVs) are increasing intensively due to its capability to perform Vertical Take-Off and Landing (VTOL), in addition to the forward flight mode. With the capability, the hybrid UAVs are highly on demand in various industries such as military, agricultural, and geographic. Unfortunately, hybrid UAVs are facing certain challenges such as the strong crosswind condition during hover mode, complexity in transition flight regime analysis, and the high-cost prototype manufacturing. Taking the challenges into consideration, the fixed-wing VTOL UAV was designed and developed with few focuses during the entire process. The design was optimized to achieve the best flight performance in terms of weight estimation, aerodynamic, propulsion, and stability and control by using Matlab, XFLR5, and Computer Aided Design (CAD) such as SolidWorks. With the allocated time and financial support, a low-cost prototype was developed and fabricated according to the optimized result. Lay-up process was integrated into the prototype fabrication to ensure the high strength structure. Next, testing in actual conditions was needed that led the prototype to flight test. The fixed-wing VTOL UAV was able to take-off vertically with an unstable flight that controlled manually. Therefore, possible next step is to design a controller that allows the fixed-wing VTOL UAV to be controlled and stabilized autonomously in order to achieve the best flight performance.